2018
DOI: 10.20964/2018.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High Concentration of Chloride Ions on the Corrosion Behaviour of X80 Pipeline Steel in 0.5 mol L-1 NaHCO3 Solutions

Abstract: A dynamic potential polarization technique and electrochemical impedance spectroscopy (EIS) measurements were used to explore the effects of a high concentration of chloride ions on the electrochemical corrosion properties of X80 pipeline steel in 0.5 mol L -1 NaHCO 3 solutions. The surface corrosion morphology of X80 steel after polarization measurements was observed by scanning electron microscopy (SEM). The electrochemical results showed that the corrosion-product resistance and charge-transfer resistance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have suggested that the presence of chloride ions and high levels of humidity offer the right conditions for corrosion onset, which have a significant impact on the integrity and durability of metallic structures. Chloride ion thresholds for corrosion initiantion has been identified to be within the range of 100 ppm and 3500 ppm depending on the type of metal alloy, temperature and pH [30,31].…”
Section: Motivationmentioning
confidence: 99%
“…Studies have suggested that the presence of chloride ions and high levels of humidity offer the right conditions for corrosion onset, which have a significant impact on the integrity and durability of metallic structures. Chloride ion thresholds for corrosion initiantion has been identified to be within the range of 100 ppm and 3500 ppm depending on the type of metal alloy, temperature and pH [30,31].…”
Section: Motivationmentioning
confidence: 99%